2021
DOI: 10.1371/journal.pone.0259551
|View full text |Cite
|
Sign up to set email alerts
|

A rapid real-time polymerase chain reaction-based live virus microneutralization assay for detection of neutralizing antibodies against SARS-CoV-2 in blood/serum

Abstract: Background Individuals recovering from COVID-19 are known to have antibodies against the Spike and other structural proteins. Antibodies against Spike have been shown to display viral neutralization. However, not all antibodies against Spike have neutralizing ability although they may be cross-reactive. There is a need for easy-to-use SARS-CoV-2 neutralizing assays for the determination of virus-neutralizing activity in sera of individuals. Here we describe a PCR-based micro‐neutralization assay that can be us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…A study from Sri Lanka by Jeewandara et al showed that BBIBP‐CorV vaccination resulted in 95% seroconversion at 6 weeks and also found antibodies associated with neutralizing activity to SARS‐CoV‐2 27 . Earlier, we reported IgG to RBD measured in both COVID‐19 convalescent and healthy individuals to be associated with neutralizing activity to SARS‐CoV‐2 28 . Here, we found IgG seropositivity at 8 weeks postvaccination in participants without a history of COVID‐19 to be lower at, 89.1% to Spike and 64.9% to RBD.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A study from Sri Lanka by Jeewandara et al showed that BBIBP‐CorV vaccination resulted in 95% seroconversion at 6 weeks and also found antibodies associated with neutralizing activity to SARS‐CoV‐2 27 . Earlier, we reported IgG to RBD measured in both COVID‐19 convalescent and healthy individuals to be associated with neutralizing activity to SARS‐CoV‐2 28 . Here, we found IgG seropositivity at 8 weeks postvaccination in participants without a history of COVID‐19 to be lower at, 89.1% to Spike and 64.9% to RBD.…”
Section: Discussionmentioning
confidence: 56%
“…27 Earlier, we reported IgG to RBD measured in both COVID-19 convalescent and healthy individuals to be associated with neutralizing activity to SARS-CoV-2. 28 Here, we found IgG seropositivity at 8 weeks postvaccination in participants without a history of COVID-19 to be lower at, 89.1% to Spike and 64.9% to RBD. Our data correlates with previous reports from Pakistan that showed 78% of individuals to display antibody responses to RBD after vaccination with BBIBP-CorV.…”
Section: Sars-cov-2 Antigen Induced T Cell Responses To Epitopes Of C...mentioning
confidence: 47%
“…In this data set, we were not able to directly test all samples here for virus neutralizing activity. However, we have shown IgG to RBD as detected by the assay for neutralizing activity against SARS-CoV-2 and found this to correlation with IgG titers [ 33 ]. Therefore, we speculate that RBD antibodies found in our healthy blood donors reflected previous SARS-CoV-2 infection whilst a higher frequency of spike antibodies could be associated with cross-reactive antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This general test principle was previously demonstrated to be suitable also for other RNA viruses ( 41 ). Moreover, Abidi et al recently reported that RT-PCR can detect antiviral activity in selected sera with high anti-RBD antibody titers in a SARS-CoV-2 neutralization assay ( 42 ). However, the authors did not evaluate if their method can be used to determine neutralization titers, since only three different serum dilutions were used, and 13 out of the 19 sera exhibited 100% virus neutralization for all tested concentrations.…”
Section: Discussionmentioning
confidence: 99%